Ekonomiczny wymiar współpracy Polskiej Rzeczpospolitej Ludowej z Polonią na przykładzie działalności przedsiębiorstw polonijno-zagranicznych = Economic Aspect of the Polish People`s Republic Cooperation with the Polish Diaspora exemplified by the Activities of Foreign and Diaspora Companies - Nitschke, Bernadetta (1964- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Polish policy towards the Polish Diaspora changed in the 70s of the 20th century. It became more open and intense. The changes were initiated by the First Secretary of the CentralCommittee of the Polish United Workers Party - the then Edward Gierek. The economic aspectbecame one of the most important concerning the cooperation between the Diaspora and Poland.Moreover, the economic situation made it possible for the foreign managers to run a business inPoland. The Council of Ministers Decree dated 14th of May,1976 made it attainable.
Keywords: polonia; historia gospodarcza; stosunki zagraniczne; polityka zagraniczna; PRL; history of economy; international relationships; Polish Republic of People; foreign policy